أهمية تكنولوجيات الإعلام والاتصال بالنسبة للداعية التلفزيون والأنترنت نموذجا - قلوح, لطفي (جامعة الوادي - University of Eloued, 2021)
هدف البحث إلى بيان أهمية استغلال واستفادة الدعاة من تكنولوجيا الإعلام والاتصال في العصر الحديث. وقد خلص البحث إلى أنه على الداعية الاستفادة من تكنولوجيا الإعلام والاتصال لنشر الدعوة والوصول إلى أكبر عدد من المدعوين في العالم، لتصل رسالة الإسلام واضحة مفهومة خالية من أي لبس أو تشويه، لتحقيق مصلحة الإنسانية في الدنيا والآخرة، وعدم الاكتفاء بالوسائل التقليدية المحدودة التأثير والانتشار. The aim of the research is to show the importance of the preachers' exploitation of information and communication technology in the modern era. The research concluded that the preacher should take advantage of information and communication technology to spread the call and reach the largest number of invitees in the world, so that the message of Islam is clear and understandable free of any confusion or distortion, to achieve the interest of humanity in this world and the hereafter, and not be satisfied with the traditional means of limited influence and spread.
The importance of information and communication technologies for the preacher Television and the Internet as a model
مقال
Keywords: تكنولوجيا الإعلام والاتصال، الداعية، الأنترنت، التلفاز; Information and communication technology, preacher, Internet, television.